Molecular recognition in G-quadruplexes : from G-tetrad formation to protein binding - Cheong, Vee Vee (2015)
Under physiological conditions, guanine-rich oligonucleotides may assemble into a four-stranded structure, the G-quadruplex. G-quadruplexes may cause genomic instability in cells, requiring modulation by proteins. As guanine-rich DNA is susceptible to DNA damage, a G-quadruplex with complementary 8-oxoguanine-xanthine mutation was characterized. Its structure resolved in K+ highly resembles the wild-type G-quadruplex. In contrast, the non-complementary arrangement of 8-oxoguanine and xanthine within a G-tetrad inverts the polarity of the modified tetrad. We demonstrated Rhau53-105 to preferentially bind parallel G-quadruplexes, and identified residues 53–70 (Rhau18) as the determinant G-quadruplex binding region. We present the solution structure of a G-quadruplex bound with peptide, and identified hydrophobic, stacking and electrostatic interactions between the two biomolecules. BLM is a RecQ helicase that selectively resolves G-quadruplexes. The RQC domain (BLMRQC) is highly soluble and the solution structure of BLMRQC adopts a winged-helix motif. BLMRQC binds DNA weakly and requires the zinc-binding domain for tight G-quadruplex binding.